Design Optimization And Development Of Portable Vacuum Clamping (VacCLAMP) Based On Machining Performances - Ab Wahab, Norfariza; Md. Rozali, Sahazati; Abdul Rahman, Nabil Haikal; Nordin, Abd Khahar; Che Amran, Aliza; Mohamad Saleh, Saleha (IJENS Publisher, 2018)
Manufacturing and workshop practices have become important in the industrial environment to produce products for the service of mankind. Clamping in milling usually use tools and holding devices such as vise to clamp workpiece. The purpose of this project is to develop and optimize for portable vacuum clamping. The method is to develop and optimize of apply the vacuum clamping method on milling machine. Then, the design of the vacuum clamping is being optimized. After product is finished, a testing is done on the vacuum clamping to evaluate and experiment the result of product. The result shows that vacuum clamping has better surface roughness result which total of 1.696μm. As a conclusion, all the various result of analysis is taken and vacuum clamping can be able to be apply and used for teaching purpose.